884 Improving the Analgesia Prescribing Compliance to NICE Guidelines (NG118) In Suspected Renal Colic Patients Using a Proforma. (12th October 2021) - Marques, S D B; Cheah, W; Smith, C; Kailasa, A; Alexandrou, K
Abstract: Aim: To improve analgesia prescribing for patients admitted with suspected renal colic in line with NICE guidelines (NG118) in an acute district general hospital using a proforma. Method: In the first cycle, a retrospective review of 16 patients who presented with renal colic to the emergency department or surgical assessment unit was performed and the analgesia prescribing was recorded. A unique analgesia prescribing proforma was then developed using NICE guidelines (NG118) including the use of NSAIDS as first-line when there are no contra-indications, intravenous paracetamol, opioid analgesics and omitting antispasmodics. Following implementation of the proforma, a prospective review of 18 patients were included in the second cycle and the prescribing compliance were compared. Results: Study included 34 patients who presented with suspected renal colic over a 3-month period. In the first cycle, 19% of patients had appropriate analgesia prescribed which were compliant with NICE guidelines. In cycle 2, 89% of patients had appropriate analgesia prescribed. In particular, the inappropriate prescription of antispasmodics has improved significantly (38 % in cycle 1 vs 0 % in cycle 2). Conclusions: A proforma can serve as a useful 'checklist' for analgesia prescribing and improve the symptomatic relief for patients presenting with suspected renal colic in line with NICE quality standards.